Methyl-cyclopentadienyl Ruthenium Compounds with 2,2′-Bipyridine Derivatives Display Strong Anticancer Activity and Multidrug Resistance Potential - Mendes, Paulo J. (2019)
New ruthenium methyl-cyclopentadienyl compounds bearing bipyridine derivatives with the general formula [Ru(η5-MeCp)(PPh3)(4,4′-R-2,2′-bpy)]+ (Ru1, R = H; Ru2, R = CH3; and Ru3, R = CH2OH) have been synthesized and characterized by spectroscopic and analytical techniques. Ru1 crystallized in the monoclinic P21/c, Ru2 in the triclinic P1̅, and Ru3 in the monoclinic P21/n space group. In all molecular structures, the ruthenium center adopts a “piano stool” distribution. Density functional theory calculations were performed for all complexes, and the results support spectroscopic data. Ru1 and Ru3 were poor substrates of the main multidrug resistance human pumps, ABCB1, ABCG2, ABCC1, and ABCC2, while Ru2 displayed inhibitory properties of ABCC1 and ABCC2 pumps. Importantly, all compounds displayed a very high cytotoxic profile for ovarian cancer cells (sensitive and resistant) that was much more pronounced than that observed with cisplatin, making them very promising anticancer agents.